(untitled) (Prithvi Academic Journal, 2022)
Within the territory of Nepal and its vicinities like India, Myanmar and Bhutan, the Nepali language is used as a means of wider communication. Apart from this, it has become a fertile field of research for linguists, language-based researchers and language teachers. With this assumption, this article aimed to investigate the typical (that are culture-specific) terms of the Nepali language. To achieve this objective, the study employed a case study design that took Nepali culture-specific terms as a case and used document analysis for the interpretation of the information in the selected language based on the framework of words and phrases. For maintaining readability and intelligibility to the global readership, the typical Nepali terms have been glossed in English. The main finding is that the Nepali language is rich in its cultural terms that comprise words and phrases. This study can contribute to the linguists, translators and pedagogues for the frame of reference for further exploration of the rich field of study, reaching to the wider readership.